Impact of Climate Change on Indigenous People: A Study on Garo Community in Haluaghat, Mymensingh - MD. Mahmudul Hasan Rifat (HISTORICAL: Journal of History and Social Sciences, 2025)
Climate change poses significant challenges worldwide, disproportionately affecting vulnerable communities, particularly indigenous groups who are closely tied to their natural environments. This study focuses on assessing the impact of climate change on the Garo community in Gazirbhita Union, Haluaghat Upazila, Mymensingh. The research aims to explore the multifaceted effects of climate change on the socio-economic, cultural, and environmental aspects of the Garo people. Using a sample size of 95 respondents, qualitative and quantitative methods are employed to gather insights into their experiences, traditional knowledge, and adaptive strategies. The findings reveal that climate-induced changes, such as erratic rainfall, rising temperatures, and increased frequency of extreme weather events, have significantly affected agriculture, livelihoods, and biodiversity. Furthermore, the community's indigenous knowledge and resilience play a pivotal role in adaptation, yet these strategies face challenges due to limited resources and external pressures. This research underscores the urgent need for inclusive policies that integrate indigenous knowledge into climate adaptation strategies and enhance the Garo community’s resilience to future climate shocks.